2011
DOI: 10.1016/j.bbamcr.2010.12.023
|View full text |Cite
|
Sign up to set email alerts
|

Calmyrin1 binds to SCG10 protein (stathmin2) to modulate neurite outgrowth

Abstract: Calmyrin1 (CaMy1) is an EF-hand Ca(2+)-binding protein expressed in several cell types, including brain neurons. Using a yeast two-hybrid screen of a human fetal brain cDNA library, we identified SCG10 protein (stathmin2) as a CaMy1 partner. SCG10 is a microtubule-destabilizing factor involved in neuronal growth during brain development. We found increased mRNA and protein levels of CaMy1 during neuronal development, which paralleled the changes in SCG10 levels. In developing primary rat hippocampal neurons in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2014
2014
2017
2017

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 64 publications
0
5
0
Order By: Relevance
“…In the top list of upregulated expressions, there were several genes involved in mRNA processing and translation initiation such as heterogeneous nuclear ribonucleoproteins (HNRNP symbol), ribosomal proteins (RP symbol) and eukaryotic translation initiation factors (EIF and EEF symbols). The most significantly downregulated gene was STMN2 which encodes stathmin-like 2, a protein primarily known for its role in dynamics of microtubules during neuronal growth [ 13 ] but also thought to be involved in the regulation of the fate of adipocyte differentiation [ 14 ].…”
Section: Resultsmentioning
confidence: 99%
“…In the top list of upregulated expressions, there were several genes involved in mRNA processing and translation initiation such as heterogeneous nuclear ribonucleoproteins (HNRNP symbol), ribosomal proteins (RP symbol) and eukaryotic translation initiation factors (EIF and EEF symbols). The most significantly downregulated gene was STMN2 which encodes stathmin-like 2, a protein primarily known for its role in dynamics of microtubules during neuronal growth [ 13 ] but also thought to be involved in the regulation of the fate of adipocyte differentiation [ 14 ].…”
Section: Resultsmentioning
confidence: 99%
“…2009). A role for internal reorganization of neural structures during changes in brain size (Barton and Harvey 2000) is suggested by an enrichment of genes involved in cell projection organization among those genes that coevolve with brain mass, including CIB1 and PTPRG (Bouyain and Watkins 2010; Sobczak et al. 2011).…”
Section: Discussionmentioning
confidence: 99%
“…Calcium is a ubiquitous second messenger and is important in the control of neuronal migration and neurite development (Komuro and Kumada, 2005; Zheng and Poo, 2007). Studies have shown that EF-hand proteins such as MACF1, caltubin, and calmyrin1 regulate cytoskeletal components through EF-hand motifs during neurite outgrowth (Nejatbakhsh et al, 2011; Sanchez-Soriano et al, 2009; Sobczak et al, 2011), suggesting potential roles of EF-hand motif in MACF1 activity during neuronal development. Future studies would address whether the actin-microtubule bridging property of MACF1 is dependent on calcium binding in the EF-hand motif.…”
Section: Discussionmentioning
confidence: 99%